(untitled) (Italian Journal of Public Health, 2009)
Aim: Temporomandibular disorders (TMD) occur frequently in the population and measuring health-related quality of life may prove to be a very useful complementary measure. The aim of our study was to evaluate both the correlation and the agreement between SF-36 and the Axis II of Research Diagnostic Criteria for TMD in the assessment of health-related quality of life in TMD patients. Methods: This study was conducted on consecutives patients referred to our Department from 1 July 2007 to 31 January 2008. Each subject completed the Axis II and SF-36 questionnaires. Correlation of the SF-36 vs. the Axis II scales (graded chronic pain, depression, somatization with and without pain, jaw disability checklist) was calculated using non-parametric Spearmen coefficient. Results: The examined sample was composed by 146 subjects (30 males, 116 females; mean age 35,2 ±14,38 years). There isn’t significant gender difference in age (p=0.083). All the considered Axis II scales are significantly inversely related with all the SF-36 domains. Conclusion: Due to the good agreement with Axis II, SF-36 can be used for measuring Health Related Qualit of Life in TMD patients.